Decreased Type I Interferon Production by Plasmacytoid Dendritic Cells Contributes to Severe Dengue - Upasani, Vinit; Scagnolari, Carolina; Frasca, Federica; Smith, Nikaïa; Bondet, Vincent; Vanderlinden, Axelle; Lay, Sokchea; Auerswald, Heidi; Heng, Sothy; Laurent, Denis; Ly, Sowath; Duong, Veasna; et al. (Frontiers in Immunology, 2020)
The clinical presentation of dengue virus (DENV) infection is variable. Severe complications mainly result from exacerbated immune responses. Type I interferons (IFN-I) are important in antiviral responses and form a crucial link between innate and adaptive immunity. Their contribution to host defense during DENV infection remains under-studied, as direct quantification of IFN-I is challenging. We combined ultra-sensitive single-molecule array (Simoa) digital ELISA with IFN-I gene expression to elucidate the role of IFN-I in a well-characterized cohort of hospitalized Cambodian children undergoing acute DENV infection. Higher concentrations of type I IFN proteins were observed in blood of DENV patients, compared to healthy donors, and correlated with viral load. Stratifying patients for disease severity, we found a decreased expression of IFN-I in patients with a more severe clinical outcome, such as dengue hemorrhagic fever (DHF) or dengue shock syndrome (DSS). This was seen in parallel to a correlation between low IFNα protein concentrations and decreased platelet counts. Type I IFNs concentrations were correlated to frequencies of plasmacytoid DCs, not DENV-infected myloid DCs and correlated inversely with neutralizing anti-DENV antibody titers. Hence, type I IFN produced in the acute phase of infection is associated with less severe outcome of dengue disease.